Association of common mental disorder symptoms with health and healthcare factors among women in rural western India: results of a cross-sectional survey. Issue 7 (7th July 2016) - Soni, Apurv; Fahey, Nisha; Byatt, Nancy; Prabhakaran, Anusha; Moore Simas, Tiffany A; Vankar, Jagdish; Phatak, Ajay; O'Keefe, Eileen; Allison, Jeroan; Nimbalkar, Somashekhar
Abstract : Objectives: Information about common mental disorders (CMD) is needed to guide policy and clinical interventions in low-income and middle-income countries. This study's purpose was to characterise the association of CMD symptoms with 3 inter-related health and healthcare factors among women from rural western India based on a representative, cross-sectional survey. Setting: Surveys were conducted in the waiting area of various outpatient clinics at a tertiary care hospital and in 16 rural villages in the Anand district of Gujarat, India. Participants: 700 Gujarati-speaking women between the ages of 18–45 years who resided in the Anand district of Gujarat, India, were recruited in a quasi-randomised manner. Primary and secondary outcomes measures: CMD symptoms, ascertained using WHO's Self-Reporting Questionnaire-20 (SRQ-20), were associated with self-reported (1) number of healthcare visits in the prior year; (2) health status and (3) portion of yearly income expended on healthcare. Results: Data from 658 participants were used in this analysis; 19 surveys were excluded due to incompleteness, 18 surveys were excluded because the participants were visiting hospitalised patients and 5 surveys were classified as outliers. Overall, 155 (22·8%) participants screened positive for CMD symptoms (SRQ-20 score ≥8) with most (81.9%) not previously diagnosed despite contact with healthcare provider in the prior year. On adjusted analyses, screening positive for CMD symptoms was associated with worse category in self-reported health status (cumulative OR=9.39; 95% CI 5·97 to 14·76), higher portion of household income expended on healthcare (cumulative OR=2·31; 95% CL 1·52 to 3.52) and increased healthcare visits in the prior year (incidence rate ratio=1·24; 95% CI 1·07 to 1·44). Conclusions: The high prevalence of potential CMD among women in rural India that is unrecognised and associated with adverse health and financial indicators highlights the individual and public health burden of CMD.